2014
DOI: 10.2460/javma.245.8.906
|View full text |Cite
|
Sign up to set email alerts
|

International survey of veterinarians to assess the importance of competencies in professional practice and education

Abstract: Results indicated a general consensus regarding the importance of specific types of competencies in veterinary professional practice and education. Further research into the definition of competencies essential for veterinary professionals is needed to help inform an international dialogue on the subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
(28 reference statements)
0
11
0
1
Order By: Relevance
“…The role that is addressed in these answers (and which should be more taken into account in veterinary training than it has been the case so far from the participants" point of view) is the role of the veterinarian as an entrepreneur. Knowledge about entrepreneurship has been identified in various studies as a crucial competence of veterinarians (Bachynsky et al, 2013;Bok et al, 2014;Cake et al, 2014;Cake et al, 2016). German farm veterinarians join these voices that underline the importance of the corresponding skills.…”
Section: Discussionmentioning
confidence: 99%
“…The role that is addressed in these answers (and which should be more taken into account in veterinary training than it has been the case so far from the participants" point of view) is the role of the veterinarian as an entrepreneur. Knowledge about entrepreneurship has been identified in various studies as a crucial competence of veterinarians (Bachynsky et al, 2013;Bok et al, 2014;Cake et al, 2014;Cake et al, 2016). German farm veterinarians join these voices that underline the importance of the corresponding skills.…”
Section: Discussionmentioning
confidence: 99%
“…The WBAs are organized around competency domains that are described in the VetPro-competency framework (see Fig. 1; [1416]). The assessment information is collected in a digital portfolio for which the student bears responsibility.…”
Section: Methodsmentioning
confidence: 99%
“… Study 2 indicated that from an international perspective there is a high degree of consensus amongst veterinarians on what could be expected from a veterinary professional and what should be taught in veterinary education. The VetPro framework proved to be a valid and valuable starting point for opening up an international discourse on the definition of competent veterinary professionals [ 17 ]. The implementation of an integrative competency-based approach to learning and assessment in undergraduate veterinary education demonstrated two main repetitive challenges.…”
Section: Resultsmentioning
confidence: 99%